2010
DOI: 10.1055/s-0030-1250407
|View full text |Cite
|
Sign up to set email alerts
|

Protoflavonoids from Ferns Impair Centrosomal Integrity of Tumor Cells

Abstract: Six protoflavonoids, including two new compounds, were isolated during a large scale screening of fern extracts for original interaction with mitosis. The new compounds isolated from PHEGOPTERIS decursive-pinnata and EQUISETUM fluviatile were 2',3'-dihydroprotogenkwanone (1) and 2',3'-dihydro-2'-hydroxyprotoapigenone (2). Known compounds were: protoapigenone, protogenkwanone, protoapigenin, and 4'- O- β-D-glucopyranosyl protoapigenin. They showed a cytotoxic activity against HeLa cells at a micromolar level. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…() isolated several lower molecular weight phenolic glycosides from E. r. debile including equisetumoside D, which has been found to be cytotoxic against Hep‐G2 cells (IC 50 = 1.12 µg/mL) and RD rhabdosarcoma cells (IC 50 = 0.25 µg/mL). In the circumboreally distributed Water Horsetail ( Equisetum fluviatile L.), protoapigenone was accompanied by its 2′,3′‐dihydro‐2′‐hydroxy derivative, which also possessed cytotoxic activity (Pouny et al ., ).…”
Section: Anticancer Activity Of Extracts and Compounds Isolated From mentioning
confidence: 97%
See 2 more Smart Citations
“…() isolated several lower molecular weight phenolic glycosides from E. r. debile including equisetumoside D, which has been found to be cytotoxic against Hep‐G2 cells (IC 50 = 1.12 µg/mL) and RD rhabdosarcoma cells (IC 50 = 0.25 µg/mL). In the circumboreally distributed Water Horsetail ( Equisetum fluviatile L.), protoapigenone was accompanied by its 2′,3′‐dihydro‐2′‐hydroxy derivative, which also possessed cytotoxic activity (Pouny et al ., ).…”
Section: Anticancer Activity Of Extracts and Compounds Isolated From mentioning
confidence: 97%
“…Pouny et al . () used bioactivity‐guided fractionation, observing the effect on the viability of HeLa cells (ATP luminescence assay) as well as phenotypic changes including the loss of centrosomal γ‐tubulin labelling in both mitotic and interphasic cells. By means of this method, these authors identified the protoflavonoid protogenkwanone (7‐ O ‐methylprotoapigenone) (Fig.…”
Section: Anticancer Activity Of Extracts and Compounds Isolated From mentioning
confidence: 99%
See 1 more Smart Citation
“…Typically found in fern species (e.g., Thelypteris and Pseudophegopteris), protoflavones are rare natural flavonoids with an unusual non-aromatic B-ring [8]. Several of these compounds have been found to exert promising antitumor effects on a wide variety of cell lines in vitro [9][10][11][12][13] and various xenograft models in vivo [12,[14][15][16]. Protoflavonoids were reported to induce apoptosis and cause S and G2/M phase cell cycle arrest [17,18], and this is closely associated with their ability to induce oxidative stress [19].…”
Section: Introductionmentioning
confidence: 99%
“…Efeito dos substituintes na atividade antitumoral das protoflavonas Nakagawa-Goto;. et al, 2008;et al, 2008;Lin, A. S. et al, 2005;Pouny et al, 2011;Wei et al, 2011) (Pouny et al, 2011;Wada, H. et al, 1987) Antitumoral (Lin, A. S. et al, 2005;Wei et al, 2012)…”
Section: Figuraunclassified